Overflow, Circulation & Biodiversity - Cruise No. MSM21/2 - June 25 - July-24, 2012 - Reykjavik (Iceland) - Nuuk (Greenland) - Kieke, Dagmar; Böke, Wolfgang; Denker, Claudia; Grobelny, Alex; Hertzberg, Stefan; Hogue, Brian; Horn, Myriel; Kattein, Ole; Löb, Jonas; Ludwig, Reimund; Mertens, Christian; Müller, Vasco; et al. (DFG-Senatskommission für Ozeanographie, 2014)
To a major extent cruise MSM21/2 was dedicated to the recovery and deployment of longterm observatories (deep-sea moorings and inverted echo-sounders equipped with pressure sensors, PIES) installed at key locations of the western subpolar North Atlantic. Associated research objectives deal with estimating variations of the large-scale circulation. Altogether, three mooring arrays were serviced. The array installed across the Charlie Gibbs Fracture Zone in 2010 by the group from the Woods Hole Oceanographic Institution (WHOI) was successfully recovered (eight moorings). Three deep-sea moorings maintained by the German Federal Maritime and Hydrographic Agency (BSH) at the western side of the Mid-Atlantic Ridge (MAR) were successfully exchanged. While the mooring array of the University of Bremen deployed across the Deep Western Boundary Current east of Flemish Cap was successfully recovered, a rope in the lower part of mooring BM-22 broke during redeployment. All sensors could be received back, but the acoustic releases were lost. The mooring could, however, be installed again due to provision of releases by the BSH group. The deployment of a fourth additional mooring at the MAR had to be canceled, since this, while already installed, became entangled with the conducting wire during a hydrographic cast. The mooring was completely recovered, but a mooring rope tore apart during subsequent redeployment, and a pair of acoustic releases was lost. In Flemish Pass, the array jointly operated by the Universities of Bremen and Hamburg and consisting of two moorings, was successfully installed along 47°N. All visited PIES delivered time series of high quality. Two instruments, nevertheless, showed oil leakages after having been recovered, which prevented their reinstallation along 47°N in the Newfoundland Basin. Altogether, 80 hydrographic casts with tracer sampling at key stations were carried out. The last cast had to be aborted, the subsequent scientific program terminated and the ship's track considerably changed due to a severe storm system located to the south of Greenland that enforced a detour on the way to Nuuk. : MARIA S. MERIAN-Berichte